Preparation of succinylated cellulose membranes for functionalization purposes. (5th September 2016) - Ribeiro-Viana, Renato M.; Faria-Tischer, Paula C.S.; Tischer, Cesar A.
Highlights: Succinylation of cellulose is achieved with minimal interference on membrane structure. Chemical modification took place mainly on the surface of membrane. Carboxyls appended on the membrane permitted a functionalization with a protein. Abstract: The anhydroglucose chains of cellulose possess hydroxyls that facilitate different chemical modification strategies to expand on, or provide new applications for membranes produced by the bacteria Gluconacetobacter xylinus . Conjugation with biomolecules such as proteins, especially by the amine groups, is of great value and interest for the production of biomaterial derivatives from bacterial cellulose. To assist in these modifications, cellulose was succinylated in order to prevent steric hindrance and to create an attachment point for conjugation. Bacterial cellulose membranes were first treated in dichloromethane and reacted with succinic anhydride through a series of conditions. The membrane structure remained intact after these first processes and the product was confirmed by Infra-Red spectroscopy and solid state nuclear magnetic resonance and characterized by X-ray diffraction, thermogravimetry and atomic force microscopy. Hydrolyzed collagen was used as a model protein of interest to be conjugated to these membranes, which furnished a biomaterial functionalized over its surface.